An admission control and traffic engineering model for Diffserv-MPLS networks - Mantar, Haci Ali (Springer Verlag, 2006)
This paper presents a Bandwidth Broker (BB) based admission control and traffic engineering model for Diffserv supported MPLS networks. The proposed model uses a multi-path model in which several paths are pre-established between each ingress-egress router pair. As a central agent in each domain, the BB performs admission control on behalf of its entire domain via pre-established paths. The proposed model reduces the network congestion by adaptively balancing the load among multiple paths based on measurement of path utilization state. It increases the network core scalability by minimizing the core routers' state maintenance and signaling operation. The experimental results are provided to verify the achievements of our model. © Springer-Verlag Berlin Heidelberg 2006. © 2020 Elsevier B.V., All rights reserved.
9th Asia-Pacific Network Operations and Management Symposium, APNOMS 2006 -- Busan -- 68456
Keywords: Adaptive systems; Congestion control (communication); Mathematical models; Routers; Signal processing; Telecommunication traffic; Admission control; Bandwidth Broker (BB); Diffserv-MPLS networks; Traffic engineering model; Telecommunication networks